Azo dye adsorption effect induced by elliptically polarized light in azo dye-doped liquid crystals - Fuh, Andy Ying-Guey; Chen, Yuan-Di; Liu, Cheng-Kai; Cheng, Ko-Ting (Dyes and pigments, 2012)
This study elucidates the azo dye adsorption effect induced by elliptically polarized light in azo dye-doped liquid crystals (ADDLCs). Experimental results reveal that the light-induced molecular reorientation that is caused by the adsorbed azo dyes declines as the absolute value of the ellipticity of the pumping beam, having a proper selectively fixed light intensity or a proper selectively fixed light component along the direction of major axis, increases. The long axes of the adsorbed dyes are found to be independent of the sign of the light ellipticity, but they do depend on the direction of the major or minor axis of the elliptically polarized light. Notably, the tilt angle in LC alignment is not observed in this experiment. Additionally, neither twist angles nor tilt angles can be induced using a circularly polarized pumping beam. ► The adsorption of azo dyes in LCs induced by elliptically polarized light is shown. ► The twist angle declines as the absolute value of the ellipticity increases. ► The long axes of the adsorbed dyes depend on the major/minor axis of pumping light. ► The tilt angle in LC alignment is not observed here. ► Neither twist nor tilt angle can be formed using a circularly polarized beam.